Immunoglobulin G glycome in colorectal cancer - Vučković, Frano (Clin Cancer Res, 2016)
PURPOSE: Alternative glycosylation has significant structural and functional consequences on immunoglobulin G and consequently also cancer immunosurveilance. Due to technological limitations, the effects of highly heritable individual variations and the differences in the dynamics of changes in IgG glycosylation on colorectal cancer (CRC) were never investigated before. EXPERIMENTAL DESIGN: Using recently developed high-throughput UPLC technology for IgG glycosylation analysis we analysed IgG glycome composition in 760 patients with CRC and 538 matching controls. Effects of surgery were evaluated in 28 patients sampled before and three times after surgery. A predictive model was built using regularized logistic regression and evaluated using a 10-cross validation procedure. Furthermore, IgG glycome composition was analysed in 39 plasma samples collected before initial diagnosis of CRC. RESULTS: We have found that CRC associates with decrease in IgG galactosylation, IgG sialylation and increase in core-fucosylation of neutral glycans with concurrent decrease of core fucosylation of sialylated glycans. While a model based on age and sex did not show discriminative power (AUC=0.499), the addition of glycan variables into the model considerably increased the discriminative power of the model (AUC=0.755). However, none of these differences were significant in the small set of samples collected before the initial diagnosis. CONCLUSIONS: Considering the functional relevance of IgG glycosylation for both tumour immunosurveilance and clinical efficacy of therapy with monoclonal antibodies, individual variation in IgG glycosylation may turn out to be important for prediction of disease course or the choice of therapy, thus warranting further, more detailed studies of IgG glycosylation in CRC.